The development and status of sexual orientation discrimination under international human rights law - McGoldrick, Dominic (Oxford University Press, 2016)
This article assesses the development, status and recognition of a prohibition on sexual orientation discrimination as a matter of international human rights law. The State practice examined appears to reveal fundamental divisions on this issue. The article considers whether there are any treaty-based obligations that support the prohibition on sexual orientation as an existing right. Having examined the national, regional and international human rights jurisprudence on sexual orientation discrimination, the article considers the possible ways forward in policy terms, given the continued opposition from a significant body of States. More specifically, it discusses the most appropriate legal and strategic responses at national, regional and international levels to manage or bridge the divisions between States on the issue.